“In Limbo”—use of, and alterations to, modified diets by nursing home staff in the absence of timely specialist support - Okon, Mary; Chan, Kei Yen; O’Keeffe, Shaun T. (Frontiers in Rehabilitation Sciences, 2024)
Background: Dysphagia is common in nursing home (NH) residents. Staff may not always be able to access speech and language therapist (SLT) assessments in a timely manner and there are some reports of nurses initiating or changing modified diets in these circumstances. Methods: A mixed quantitative and qualitative approach was used to analyse responses to an online anonymized survey of senior nurses working in Irish NHs. They were asked about their experience of delays accessing SLT services and whether they would ever initiate or change modified diets. Respondents were asked if they would give water to a thirsty resident, prescribed mildly thick liquids, who demanded it on a hot day because thickened fluid was not thirst quenching. Results: Of 77 nurses surveyed, 63 (82%) responded. Three quarters reported delays accessing SLT services sometimes or often. Thirty-four (54.0%) would not give the thirsty resident water. About 70% reported that thickened fluids or modified texture diets were started without SLT sometimes or often. The main themes that emerged from the comments provided were related to the uncertainty and dilemmas created for staff and the need for better guidance and better access to SLT services. Discussion: Delays accessing SLT services are common for Irish NHs, and staff may initiate or change modified diets themselves in these circumstances. The responses suggest a widespread, and unjustified, belief that thicker or more modified is better for those with dysphagia. Clear and accurate guidance, and a better SLT service, is needed for NH staff.